2017
DOI: 10.1002/ppap.201700082
|View full text |Cite
|
Sign up to set email alerts
|

Activity of catalase enzyme in Paulownia tomentosa seeds during the process of germination after treatments with low pressure plasma and plasma activated water

Abstract: In this work we present results of two significantly different types of plasma treatment on Paulownia tomentosa Steud. seeds. In the first type, seeds were directly treated in low‐pressure plasma and then imbibed with distilled water. In the second type, an atmospheric pressure plasma was used for obtaining plasma activated water (PAW) which is then used for imbibition of seeds. The CAT activity and protein content is evaluated during 4 d following the imbibition process, i.e., immediately after the phytochrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 81 publications
3
42
0
Order By: Relevance
“…On the contrary, seeds germinated in the PAW or plants irrigated with the PAW, as it is in our experiments, showed decrease of antioxidant enzymes activity. However, the activity can also be affected by others parameters, for example, growth phase of plants . Unfortunately, there are no studies dealing with the monitoring of antioxidant enzymes activity in plants irrigated with the PAW (related to indirect plasma treatment) to make more specific conclusion.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…On the contrary, seeds germinated in the PAW or plants irrigated with the PAW, as it is in our experiments, showed decrease of antioxidant enzymes activity. However, the activity can also be affected by others parameters, for example, growth phase of plants . Unfortunately, there are no studies dealing with the monitoring of antioxidant enzymes activity in plants irrigated with the PAW (related to indirect plasma treatment) to make more specific conclusion.…”
Section: Resultssupporting
confidence: 53%
“…Several papers reported antioxidant enzymes activity and concluded that plasma in direct contact with plant cell increases the activity . On the contrary, seeds germinated in the PAW or plants irrigated with the PAW, as it is in our experiments, showed decrease of antioxidant enzymes activity. However, the activity can also be affected by others parameters, for example, growth phase of plants .…”
Section: Resultssupporting
confidence: 47%
See 1 more Smart Citation
“…In the last few years, studies have been conducted on selected species to test the effect of PAW on seed germination and plant growth …”
Section: Introductionmentioning
confidence: 99%
“…While additional techniques can be considered to observe protein folding (circular dichroism spectroscopy reference) or the introduction of backbone breaks (e.g., gel electrophoresis, besides other techniques), such experiments require additional facilities and expertise. To circumvent this, some studies use enzymes which have easy‐to‐monitor functions as models such as GapDH, RNaseA, or catalase …”
Section: Inactivation Mechanisms Of Low‐pressure Plasmasmentioning
confidence: 99%